Agricultural Land Redistribution and Land Administration in Sub-Saharan Africa : Case Studies of Recent Reforms - Byamugisha, Frank F. K. (Washington, DC: World Bank, 2014)
The six case studies in this book were prepared as background studies for a synthesis report on land administration and reform in Sub-Saharan Africa (SSA). Collectively they cover two main areas of land governance: reforms in redistributing agricultural land; and reforms in land administration. The problems in land ownership inequality and poor land administration are defined and the question of why reforms are necessary is addressed. The first two case studies focus on reforms in redistributing agricultural land in Malawi and South Africa. The Reforms in four thematic areas of land administration are addressed in the remaining case studies, encompassing experience from various countries as follows: (1) decentralizing land administration (Ethiopia, Ghana, Tanzania, and Uganda); (2) developing post-conflict land administration systems (Liberia and Rwanda); (3) reengineering and computerizing land information systems (Ghana and Uganda); and (4) improving management of government land through land inventories (Ghana and Uganda). The common elements between sometimes quite disparate experiences provide lessons of relevance to other SSA countries contemplating similar reforms.